Construct Validity of the Holistic Complementary and Alternative Medicines Questionnaire (HCAMQ)—An Investigation Using Modern Psychometric Approaches. (11th January 2011) - Kersten, Paula; White, P. J.; Tennant, A.
Abstract : The scientific basis of efficacy studies of complementary medicine requires the availability of validated measures. The Holistic Complementary and Alternative Medicine Questionnaire (HCAMQ) is one such measure. This article aimed to examine its construct validity, using a modern psychometric approach. The HCAMQ was completed by 221 patients (mean age 66.8, SD 8.29, 58% females) with chronic stable pain predominantly from a single joint (hip or knee) of mechanical origin, waiting for a hip (40%) or knee (60%) joint replacement, on enrolment in a study investigating the effects of acupuncture and placebo controls. The HCAMQ contains a Holistic Health (HH) Subscale (five items) and a CAM subscale (six items). Validity of the subscales was tested using Cronbach alpha's, factor analysis, Mokken scaling and Rasch analysis, which did not support the original two-factor structure of the scale. A five-item HH subscale and a four-item CAM subscale (worded in a negative direction) fitted the Rasch model and were unidimensional (χ 2 = 8.44, P = 0.39, PSI = 0.69 versus χ 2 = 17.33, P = 0.03, PSI = 0.77 ). Two CAM items (worded in the positive direction) had significant misfit. In conclusion, we have shown that the original two-factor structure of the HCAMQ could not be supported but that two valid shortened subscales can be used, one for HH Beliefs (four-item HH), and the other for CAM Beliefs (four-item CAM). It is recommended that consideration is given to rewording the two discarded positively worded CAM questions to enhance construct validity.